2019
DOI: 10.1016/j.echo.2019.02.014
|View full text |Cite|
|
Sign up to set email alerts
|

Global Myocardial Work Is Superior to Global Longitudinal Strain to Predict Significant Coronary Artery Disease in Patients With Normal Left Ventricular Function and Wall Motion

Abstract: Background: Noninvasive detection of functionally significant coronary artery disease (CAD) by echocardiography remains challenging, with the need to perform stress imaging to detect ischemia. The aim of this study was to determine whether global myocardial work (MW), derived from noninvasive left ventricular (LV) pressure-strain loops at rest, can predict significant CAD in patients without regional wall motion abnormalities and preserved LV ejection fraction (EF). Methods: One hundred and fifteen patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
3
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(159 citation statements)
references
References 39 publications
3
143
3
10
Order By: Relevance
“…Our further analysis of the GLS and MW parameters for LVH patients revealed that the AUCs of GWE, GWW, and GLS were signi cantly higher than that of GWI and GCW. This observation was different from that in a previous study [40], in which the AUCs of GWI and GCW in CHD patients were higher than those of GLS, GWE, and GWW. This discrepancy may be explained by the different mechanisms underlying CHD and LVH in MHD patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our further analysis of the GLS and MW parameters for LVH patients revealed that the AUCs of GWE, GWW, and GLS were signi cantly higher than that of GWI and GCW. This observation was different from that in a previous study [40], in which the AUCs of GWI and GCW in CHD patients were higher than those of GLS, GWE, and GWW. This discrepancy may be explained by the different mechanisms underlying CHD and LVH in MHD patients.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, we found that the AUCs of GWE and GWW were higher than that of GLS. In addition, one of the main limitations of GLS is its load-dependence, and the increase in afterload can reduce the wall tension, leading to a misinterpretation of the true contractile function of the myocardium [40,44]. However, for MW measurement, the non-invasive PSL integrates the afterload into the LV strain parameters, and thus MW is an optimization of the strain values [45].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] However, the GLS depends on the load, which may lead to a misinterpretation of the contractile function of the myocardium. [12][13][14] Thus, myocardial work (MW) is emerging as an alternative tool for studying LV myocardial systolic function incorporating deformation and afterload into its analysis. 15 Non-invasive MW is based on LV pressure-strain loop, which explores LV function balanced by afterload with an estimation of intraventricular pressure during a cardiac cycle 13 and can be easily calculated at the time of TTE examination using commercial software.…”
Section: Key Questionsmentioning
confidence: 99%
“…The median follow-up duration was 11 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] months. Among the whole population, 28 (24%) died including 8 (31%) with AL-CA, 18 (23%) with wild-type ATTR and 2 (17%) variant-type ATTR.…”
Section: Predictor Of All-cause Mortalitymentioning
confidence: 99%
“…Signi cantly, increased PSD in the athlete group draw attention to the points that the systolic synchronization of LV had been destroyed and nonuniformity of ventricular wall motion would reduce the mechanical e ciency during cardiac ejection. 14 In addition, the strength athletes were characterized by high LV afterload which would lead to the increased of LV stiffness. Eventually, result in more energy loss expressed as increased GWW and reduced GWE.…”
Section: Discussionmentioning
confidence: 99%